2016
DOI: 10.3109/09638288.2015.1116621
|View full text |Cite
|
Sign up to set email alerts
|

Support group programme for siblings of children with special needs: predictors of improved emotional and behavioural functioning

Abstract: Poorer emotional and behavioural functioning among participants and symptom severity of the child with special needs were associated with greater intervention effects. These results indicate that SibworkS is likely to be beneficial for siblings who have difficulties adjusting, and siblings of children with more severe special needs. Implications for Rehabilitation Siblings of children with disability are at increased risk of emotional and behavioural difficulties. Sibworks is a manualised group-based intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…Involvement in support groups has been consistently found to positively impact the mental and emotional health of caregivers [19,26,27,28]. Fortunately, it is now easier than ever for parents to locate both in-person and online support networks through the internet.…”
Section: Support Groupsmentioning
confidence: 99%
“…Involvement in support groups has been consistently found to positively impact the mental and emotional health of caregivers [19,26,27,28]. Fortunately, it is now easier than ever for parents to locate both in-person and online support networks through the internet.…”
Section: Support Groupsmentioning
confidence: 99%
“…Participants of the SibWorks support group who had a sibling with a more severe diagnosis experienced a greater benefit from the support group (Roberts, Ejova, Giallo, Strohm, & Lillie, 2016). It was also found that the emotional and behavioral functioning also increased with the group interventions.…”
Section: Support Groupsmentioning
confidence: 88%
“…However, there are limited publications about formalized safe spaces for neurotypical individuals to share their emotions and experiences. In studies done in Pakistan, Pennsylvania, Italy, and Great Britain, individuals who participated in a support group reported a higher acceptance of a SNS, in addition to higher self-concept and higher overall feeling of well-being (Dyson, 1998;Roberts et. al., 2016;Feinberg, 2013).…”
Section: Statement Of Purposementioning
confidence: 99%
See 2 more Smart Citations